Small Amplicons Mutation Library for Vaccine Screening by Error-Prone Polymerase Chain Reaction - CHENG Manman; ZHANG Yunlong; CHEN Ting; ZHANG Minmin; LU Changrui (东华大学学报（英文版）, 2023)
Q523.8; Library construction is a common method used to screen target genes in molecular biology.Most library constructions are not suitable for a small DNA library(＜100 base pair(bp))and low RNA library output.To maximize the library's complexity,error-prone polymerase chain reaction(PCR)was used to increase the base mutation rate.After introducing the DNA fragments into the competent cell,the library complexity could reach 109.Library mutation rate increased exponentially with the dilution and amplification of error-prone PCR.The error-prone PCR conditions were optimized including deoxyribonucleotide triphosphate(dNTP)concentration,Mn2+concentration,Mg2+concentration,PCR cycle number,and primer length.Then,a RNA library with high complexity can be obtained by in vitro transcription to meet most molecular biological screening requirements,and can also be used for mRNA vaccine screening.